Pancasila Sebagai Pondasi Awal Sistem Ketatanegaraan Indonesia - Achmad Syamsudin; Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Pancasila is a noble legacy that was born from the reflections of its founding fathers in the basic formulation of an independent Indonesian State. Pancasila is lifted from the original values ​​of the Indonesian people in which there are customs, culture and religion embodied in the nation's outlook on life. Pancasila is often classified as a middle ideology between the two major world ideologies that are very influential on the state. Pancasila is not communist/marxist and also not liberal/capitalist. The agreement of the Indonesian nation to make Pancasila the nation's way of life today is increasingly apprehensive due to the era of globalization. Pancasila as a weltanschaung (view of life) means that the values ​​of Pancasila are the ethics of the common life of the Indonesian people which have been rooted since ancient times. The actualization of Pancasila is the elaboration of Pancasila values ​​in the form of norms and their realization in the life of the nation and state.